PERAN MODAL SOSIAL DALAM MENINGKATKAN KESEJAHTERAAN MASYARAKAT MELALUI PEMBERDAYAAN EKONOMI PADA PENGRAJIN BATIK DI PONOROGO - Asyika Ridolla; Kasmiati Kasmiati (Investama : Jurnal Ekonomi dan Bisnis, 2022)
Goverments have rolled over many empowering programs, but sometimes such empowerment felt that it lacked a sense of community thorough. Because programs tend to be same and social lack the potential in every conceivable region of society. So, empowerment of the bottom up model that focuses more on aspects of the wealth of the natural capital of the community or society is particularly influential. Social capital is a very prominent human capital to be used in public empowerment programs. Research produced in this article aims to analyze how social capital, trust, network and norms can play a role in the economic empowerment of communities in ponorogo by using qualitative research methods using the data collection technicques of in-depth interviews of responsibility and contributing communities. The results of this study suggest that a public empowerment program through the batik ponorogo sentra of the three elements of social capital play role sustainability through a continuous interaction pattern. With leveraging empowerment social capital can go quite well. It is given the new job opportunities and the growing economic potential society. Therefore, the government needs support for the state growing.